2016
DOI: 10.1177/000313481608201234
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Calculator for Renal Complications after Colorectal Surgery Using the National Surgical Quality Improvement Program Participant Use Files

Abstract: Postoperative acute renal failure is a major cause of morbidity and mortality in colon and rectal surgery. Our objective was to identify preoperative risk factors that predispose patients to postoperative renal failure and renal insufficiency, and subsequently develop a risk calculator. Using the National Surgical Quality Improvement Program Participant Use Files database, all patients who underwent colorectal surgery in 2009 were selected (n = 21,720). We identified renal complications during the 30-day perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…In our study, independent risk factors for renal replacement were a low number of platelets before surgery, age, and especially ASA score with an increase of 15 times per ASA point (for example, ASA 3 results in a 30 times increased risk!). This correlates to the study from Ramonell, who could also identify ASA score as well as hypoalbuminemia and age as risk factors for renal failure [ 33 ]. Because age and ASA score cannot be improved, particular attention should be paid to renal function during and after surgery with thoughtful fluid therapy, an early substitution of albumin, and the start of terlipressin treatment.…”
Section: Discussionsupporting
confidence: 74%
“…In our study, independent risk factors for renal replacement were a low number of platelets before surgery, age, and especially ASA score with an increase of 15 times per ASA point (for example, ASA 3 results in a 30 times increased risk!). This correlates to the study from Ramonell, who could also identify ASA score as well as hypoalbuminemia and age as risk factors for renal failure [ 33 ]. Because age and ASA score cannot be improved, particular attention should be paid to renal function during and after surgery with thoughtful fluid therapy, an early substitution of albumin, and the start of terlipressin treatment.…”
Section: Discussionsupporting
confidence: 74%
“…The unadjusted cohort consisted of 68 studies which included 232,586,252 patients (130,605,382 women and 101,970,870 men (Figs. 3 and 4 ) [ 29 , 31 34 , 36 , 38 , 42 , 43 , 45 , 47 , 57 112 ]. Studies could be divided into 7 distinct categories.…”
Section: Resultsmentioning
confidence: 99%
“…Preexisting renal insufficiency predisposes to a large number of postoperative complications. These include wound healing disorders, pneumonia, urinary tract infections, acute renal failure, cardiac events and septic courses with multiorgan failure [ 8 ], [ 9 ]. Analogous correlations were found analyzing complications in the cohort of patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a comparatively small number of studies that examine the significance of high blood pressure for the early postoperative course after colorectal surgery. Nonsurgical complications such as renal, cardiac and pulmonary events are described after operations with curative intent [ 8 ], [ 14 ]. The present study in palliative patients also showed a hypertension-induced multivariate significant increase in postoperative medical morbidity to 1.4 times.…”
Section: Discussionmentioning
confidence: 99%